Self-assembly and nonlinear optical properties of (μ-oxo)bis[meso-tetrakis(p-bromophenyl-porphyrinato)iron(iii)]1. Issue 25 (7th July 2015) - Hou, Yuxia; Zhu, Yingzhong; Sun, Junshan; Zhang, Xiaomei; Tian, Yupeng; Jiang, Jianzhuang
<x xml:space="preserve">Abstract</x> The optical properties of [(TBPP)Fe]2O and [(TBPP)Fe]Cl have been comparatively investigated, revealing the larger TPA cross-section value of the former dimer.